2020
DOI: 10.1177/2309499020960555
|View full text |Cite
|
Sign up to set email alerts
|

Is radiofrequency ablation safe and effective in treating osteoid osteomas? A prospective single-center study with atypical cases

Abstract: Purpose: Osteoid osteomas are benign and nonprogressive lesions. The clinical presentation of osteoid osteoma is typical with night pain responsive to nonsteroidal anti-inflammatory agents. The typical radiological appearance is lucent nidus and adjacent reactive sclerosis. The most traditional management of osteoid osteoma is surgical removal which is associated with significant morbidity. This article aims to demonstrate our single-center experience of 55 patients with osteoid osteoma treated with percutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…The clinical and technical success rate was 94% after primary ablation and after re ablation of the other 2 patients we finally achieved 100% clinical and technical success rate. Our study showed a favorable outcome compatible to other international studies [17][18][19][20][21][22][23][24][25][26][27][28] . Radiofrequency ablation technique is an effective, minimally invasive and economic method of treatment.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The clinical and technical success rate was 94% after primary ablation and after re ablation of the other 2 patients we finally achieved 100% clinical and technical success rate. Our study showed a favorable outcome compatible to other international studies [17][18][19][20][21][22][23][24][25][26][27][28] . Radiofrequency ablation technique is an effective, minimally invasive and economic method of treatment.…”
Section: Discussionsupporting
confidence: 91%
“…Computed tomography (CT) guided percutaneous radiofrequency ablation in the treatment of osteoid osteoma is safe, effective with minimally invasive procedure 28 compared to previous the surgical techniques which has the drawback of difficult localisation, incomplete excision and high rate of recurrence. Literature has proven RFA in the treatment of osteoid osteoma in unattained area have achieve a favourable success rate with minimal complications and morbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data reported in the literature have demonstrated that in case of symptomatic recurrence after the first RFA treatment, re-ablation is almost always resolutive with complete disappearance of symptoms, as suggested by the revision of the literature proposed [ 10 , 16 20 , 23 25 , 36 , 39 , 42 44 , 46 , 48 50 28 – 43 , 92 , 44 51 , 54 56 ] (Table 2 ).…”
Section: Radiofrequency Ablation (Rfa)mentioning
confidence: 93%
“…It is indeed an excellent choice for the treatment of OO with less trauma, quick recovery and excellent efficacy ( 15 , 16 ). However, there are still some controversies over the treatment of proximal femoral OO considering the particular location of the nidus ( 17 , 18 ). The nidus of the proximal femur is often adjacent to the femoral sheath, and there are the main feeding vessels of the femoral head on the inside of the articular capsule.…”
Section: Introductionmentioning
confidence: 99%